A photospheric and chromospheric activity analysis of the quiescent retrograde-planet host ν Octantis A - Ramm, David J.; Robertson, P; Reffert, Sabine; Gunn, F; Trifonov, T; Pollard, K; Cantalloube, F (Monthly notices of the Royal Astronomical Society, 2021)
The single-lined spectroscopic binary nu Octantis provided evidence of the first conjectured circumstellar planet demanding an orbit retrograde to the stellar orbits. The planet-like behaviour is now based on 1437 radial velocities (RVs) acquired from 2001 to 2013. nu Oct's semimajor axis is only 2.6 au with the candidate planet orbiting about mid-way between. These details seriously challenge our understanding of planet formation and our decisive modelling of orbit reconfiguration and stability scenarios. However, all non-planetary explanations are also inconsistent with numerous qualitative and quantitative tests including previous spectroscopic studies of bisectors and line-depth ratios, photometry from Hipparcos and the more recent space missions TESS and Gaia (whose increased parallax classifies closer still to a subgiant, similar to K1IV). We conducted the first large survey of 's chromosphere: 198 H-line and 1160 indices using spectra from a previous RV campaign (2009-2013). We also acquired 135 spectra (2018-2020) primarily used for additional line-depth ratios, which are extremely sensitive to the photosphere's temperature. We found no significant RV-correlated variability. Our line-depth ratios indicate temperature variations of only +/- 4 K, as achieved previously. Our atypical analysis models the indices in terms of S/N and includes covariance significantly in their errors. The indices have a quasi-periodic variability that we demonstrate is due to telluric lines. Our new evidence provides further multiple arguments realistically only in favour of the planet.